Orgasms and hallelujahs, or, Christian spirituality and sexuality: a missionary position - Lombaard, Christo (Missionalia, 2009)
Sexuality, and integral aspect of being human, is an important and recurring theme within religious discourse. Within Christianity, sexuality usually features more as a problem than as a theme of celebration, which is to the detriment of Christians and the perception of Christianity from outside the circle of its constituents. This contribution seeks to help alter that dynamic. Embodied faith is celebrated, with themes in theological thinking and texts from the Bible that favour a positive sexuality. In conclusion, affirming sexual fulfilment as a missionary approach for Christianity is explored.
paid
Keywords: Bible – Authority; Sex – Religious aspects – Christianity; Sex in the Bible; Sexual ethics; Social ethics; Christian; South Africa – Social conditions; Spiritual life (Christianity); Ten commandments